The survival of school financing management in COVID-19 pandemic - Sujasan Sujasan; Udik Budi Wibowo (Journal of Education and Learning (EduLearn), 2021)
This study aimed to explore the survival of school financing management during the COVID-19 pandemic, to assure the quality of teaching and learning continuously. This study used a qualitative design, and data collection is carried out by observing resource persons and in-depth interviews, analysis or analysis of documentation and a combination of the three as triangulation method. The collected data were analyzed using an interactive model. The results showed that financial management strategies in managing school finances effectively and efficiently, through transparency, accountability and responsibility, are considered to have contributed to the prospects, quality, progress and sustainability of education in the midst of the COVID-19 pandemic. This is based on the fact that many quality and good schools eventually experience setbacks due to the lack of transparency, accountability and responsibility in the management of education funds. Openness in schools can promote accountability and fight corruption in education, if it is implemented effectively and any malpractice is dealt with clear consequences. The implication is the strategies of education financing management in terms of transparency, accountability and accountability need to be carry out consistently to ensure the improvement of school quality runs in a sustainable manner.